Early Childhood Development Policy Advances in Uganda - Ejuu, Godfrey (Contemporary Issues in Early Childhood, 2012)
Knowledge of the history and development of early childhood development in Uganda is paramount if we are to know how far we have come and where we are going. This article explores the introduction of early childhood development in Ugandan policy and government interventions from 1960 to 2011. Data was obtained from a review of available early childhood development policy documents, conference papers and tutorial handouts, and interviews with early childhood development professionals who were involved in the developments. The results indicate trends of events that have not been given full attention by young professionals, policy makers and academics in the field of early childhood development in Uganda.
Keywords: Early Childhood; Development Policy